1039 Nocturnal Awakening With Headache In The Sao Paulo City, Brazil In The Follow-up Study (2015) And Relationship With Insomnia. (27th April 2018) - Lucchesi, L M; Hirotsu, C; Smith, A; Prado, G; Pires, G N; Tufik, S; Togeiro, S; Poyares, D
Abstract: Introduction: There is a clear association between headache and sleep disturbances, mainly insomnia, especially when headaches occur during the night or early morning. Our group showed (EPISONO) that waking up during the night because of a headache was highly prevalent in the population of Sao Paulo (8.4%) with predominance in women. Objective: To investigate the incidence and evolution of nocturnal awakening with headache (NAH) in the EPISONO cohort after 8 years of follow up and its relationship with insomnia. Methods: From 1074 volunteers enrolled in the baseline study, 712 agreed to participate during the follow-up study (July 2015 - April 2016). Questionnaires and scales were applied face to face and a polysomnography (PSG) and actigraphy were performed. The complaint of NAH was analyzed according to a questionnaire of frequency. Frequent NAH was defined by symptoms of at least once a week, occasional by symptoms frequency of less than once a month or 1 to 3 times a month and absence. Results: From the total 712 participants, 702 had their NAH questionnaire completed in 2007. In the follow-up, 84.5% referred no NAH, 8.4% had occasional headache and 7.1% had frequent headache. Along the 8-years, the incidence of frequent and occasional NAH was 4.1% and 5.4%, respectively. After adjustment for sex and BMI, the independent factors associated with frequent NAH in comparison to no-NAH were: self-reported sleep duration (OR: 0.70, 0.58–0.85, p&lt0.0001), DSM-IV insomnia (OR: 7.75, 2.20–27.3, p=0.001), and ISI score (OR: 1.16, 1.10–1.22, p&lt0.0001), sleep onset latency from actigraphy (OR: 1.04, 1.01–1.06, p=0.012). Conclusion: The frequent NAH was independently associated with lower sleep duration, longer sleep latency from actigraphy and the presence of insomnia. Support (If Any): Associação Fundo de Incentivo à Pesquisa (AFIP) and São Paulo Research Foundation (FAPESP, #2014/15259-2).